2016
DOI: 10.1097/mbp.0000000000000196
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of two commonly used automated office blood pressure devices in the severely obese

Abstract: The accuracy of automated office blood pressure (BP) devices in severely obese individuals is unknown. In an exploratory study, we compared standardized BP measurements using a BpTRU device with those taken using a WatchBP Office monitor. Paired t-tests, Bland-Altman plots, and Pearson's correlations were used to compare devices. A total of 62 patients were analyzed: their mean age was 39.5±9.3 years and their mean BMI was 45.1±5.7 kg/m. Fifty-five patients (89%) were women and 21 (34%) had a diagnosis of hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…reporting AOBP values obtained by using the BpTRU, showed significant differences in terms of BP values between AOBP and daytime ABPM, in particular with systolic AOBP levels being lower than ABPM [50][51][52] . Another study 53 compared BpTRU readings with those taken by using the WatchBP Office in a severely obese population: the mean BpTRU values were 9.4 (11.6)/3(7.7) mmHg lower than WatchBP Office measurements, underlying a marked difference and "the need for formal validation of the devices". On the contrary, Myers et al showed no significant differences for systolic BP by using the BpTRU or Omron HEM 907 XL devices, but only 50 subjects were recruited for the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…reporting AOBP values obtained by using the BpTRU, showed significant differences in terms of BP values between AOBP and daytime ABPM, in particular with systolic AOBP levels being lower than ABPM [50][51][52] . Another study 53 compared BpTRU readings with those taken by using the WatchBP Office in a severely obese population: the mean BpTRU values were 9.4 (11.6)/3(7.7) mmHg lower than WatchBP Office measurements, underlying a marked difference and "the need for formal validation of the devices". On the contrary, Myers et al showed no significant differences for systolic BP by using the BpTRU or Omron HEM 907 XL devices, but only 50 subjects were recruited for the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its advantages, the clinical application and the accuracy of HBPM may be limited by certain conditions related either to the individual [63][64][65][66], to the procedure itself [4,67], to the oscillometric technique for BP measurement or to cuff-related issues [4,65,[68][69][70][71][72][73][74].…”
Section: Possible Difficulties With Hbpm Use In Clinical Practice (Bo...mentioning
confidence: 99%
“…The Microlife Watch BP Office has been shown to predict equal to awake ABP, left ventricular mass index, urine albumin excretion, and occurrence of CV events . Future studies are needed to validate the use of these monitors in severely obese patients . Their use among patients diagnosed with atrial fibrillation is still under question, and further studies are needed in this group.…”
Section: Factors That Influence Aobp Measurements Are the Followingmentioning
confidence: 99%